Abstract 1122‐000218: Flow Reversal After Stent Diversion Causes In‐Stent Thrombosis and Anemia‐Driven Ischemia - Adam R Blanden; Karan Philip; Hesham E Masoud (Stroke: Vascular and Interventional Neurology, 2021)
Introduction: Large symptomatic ICA aneurysms are rare, but present a life threatening risk of rupture that increases with size, female sex, and age >50 at the time of diagnosis, among other risk factors. Historically, large carotid aneurysms have been treated with intentional carotid sacrifice, requiring recruitment of contralateral, posterior, and ECA‐supplied collaterals to provide flow to the anterior circulation previously supplied by the sacrificed ICA, lest the patient experience an iatrogenic stroke. While still a viable option in some cases, flow diverting stents provide an attractive alternative to vessel sacrifice. By providing a channel for blood to bypass the aneurysm, the stent can effectively exclude the aneurism from active circulation while preserving a path for blood to travel to the anterior cerebral circulation it currently provides. Methods: Here, we present a case of a 1.3 cm symptomatic left cavernous ICA aneurysm treated with such a flow diverting stent. Results: The patient presented to the emergency department with left sided ptosis. CTA head and neck revealed the 1.3 cm left sided cavernous ICA aneurysm. She was treated endovascularly under general anesthesia with continuous intra‐operative monitoring. The procedure was complicated by iatrogenic flow reversal through the Circle of Willis at the time of stent deployment and resultant in situ thrombosis of the stent without alteration in electrical signals recorded at the scalp – thus creating a de facto carotid sacrifice without intra‐operative complication. Follow up doppler study revealed a loss of flow through the left ICA and reversal of flow through the ophthalmic artery on the left side, thus confirming ECA collateral supply to the area. Post‐op course was complicated by extensive bleeding from the scalp electrode sites used for intraoperative monitoring due to hyper‐response to aspirin‐ticagrelor dual‐antiplatelet therapy. This gave rise to a symptomatic anemia that manifested as pressure‐dependent left‐sided circulatory failure on exam – specifically hemiparesis and aphasia. The symptoms ultimately resolved with pressure augmentation, blood transfusion, and supportive care in the Neuro ICU. The patient was successfully transitioned to a general neurology floor with subsequent resolution of the anemia and, correspondingly, the symptoms. Conclusions: The patient was discharged to rehab and at 4‐month follow‐up is again living independently with no residual deficits. This case has significance for pre‐operative anti‐platelet optimization for flow diverting stents, management of post‐operative complications of flow‐diverting stent placement including thrombosis and bleeding, and optimal critical care support for patients with pressure‐dependent ischemia. Specifically, the course of the patient’s symptoms and anemia raise the question of optimal hemoglobin targets in the subset of patients with pressure‐dependent ischemia, and how to best reach those targets.